Ototyphlonemertes longissima sp. nov. (Hoplonemertea: Monostilifera: Ototyphlonemertidae), a new interstitial nemertean from the South China Sea - Liu, Hai-Long (Zootaxa, 2018)
Ototyphlonemertes longissima sp. nov is described from the South China Sea. The present species, up to 158 mm long, is about three times longer than the longest previously reported individual known in the genus. It possesses a narrow stylet basis, a bulbous proboscis diaphragm, a long middle proboscis chamber, sculptured stylets, polygranular statocysts and excretory tubules, and thus belongs to the O. macintoshi species group. The genetic divergence (average uncorrected p-distance) between O. longissima (representing a unique network in TCS analysis) and the other species (TCS networks) of genus Ototyphlonemertes is 0.135–0.185.